Ius Constituendum: Justice Concept for Substitute Heirs in Lateral Descendance under the Compilation of Islamic Law - Atis Ika Ernawati; Z. Zuhrah; I. Iksan (Jurnal Hukum Prasada, 2026)
The Compilation of Islamic Law (KHI) regulates substitute heirs only for the direct descending line, as stipulated in Article 185, thereby creating a legal vacuum for relatives in the lateral line of descent, such as siblings or nephews. This study aims to analyze the normative weaknesses in the regulation of substitute heirs under the KHI, examine the relevance of granting substitution rights to the lateral line of descent based on principles of justice and public interest (maslahah), and formulate a more responsive model of ius constituendum. This research employs a normative legal method with statutory, conceptual, and comparative approaches. Primary legal materials include the KHI, relevant regulations, and classical as well as contemporary fiqh literature, which are analyzed qualitatively. The findings indicate that the limitations of Article 185 of the KHI fail to accommodate the increasingly diverse family structures of contemporary Indonesian society. Comparative studies of inheritance systems in several Muslim countries and the views of contemporary scholars reveal the existence of ijtihad space to expand the scope of substitute heirs. This research proposes a ius constituendum concept in the form of extending the provisions on substitute heirs to include the lateral line of descent, while remaining grounded in the principles of maq??id al-shar??ah. The implication of this study is the necessity to reform the KHI in order to realize distributive justice in Islamic inheritance law in Indonesia.